Pengaruh Pola Asuh Orang Tua Terhadap Kebiasaan Konsumsi Alkohol Pada Remaja Di Kota Bitung - Kasenda, Rinna Yuanita; Kaparang, Christia G; Liu, Arnold C (Jurnal Ilmiah Wahana Pendidikan, 2024)
This article discusses the influence of parental parenting on alcohol consumption habits among teenagers in Bitung City. Research shows that parenting styles can influence alcoholism behavior in adolescents, and the influence of alcohol can have an impact especially on individual emotions and attitudes. The author suggests the importance of leading children on a good path, setting an example, and monitoring children's development positively. This research uses a qualitative approach The bibliography contains references regarding the relationship between parental parenting and alcohol consumption behavior in adolescents, as well as its influence on adolescent health and social behavior.